HUBUNGAN TINGKAT KEHARMONISAN KELUARGA DAN KEMATANGAN EMOSI TERHADAP PRESTASI BELAJAR SISWA SMA NEGERI 5 KOTA SERANG - Mela Nurhayati; Rochani; Alfiandi Warih Handoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine the relationship between family harmony (X1) and emotional maturity (X2), both partially and simultaneously, with the academic achievement (Y) of tenth-grade students at SMA Negeri 5 Serang City. This research employed a quantitative correlational approach. A total of 120 students were selected as participants using proportional random sampling. Data were collected through Likert-scale questionnaires to measure family harmony and emotional maturity, while students’ report card scores were used to assess academic achievement. The data were analyzed using multiple linear regression with SPSS version 25. The results of the partial t-test indicated that family harmony had a significant effect on academic achievement (t = 9.755, p < 0.001). Emotional maturity also showed a significant partial effect on academic achievement (t = 14.866, p < 0.001). Furthermore, the simultaneous F-test revealed that both independent variables had a very strong relationship with academic achievement (R = 0.915), contributing 83.6% (R² = 0.836) to students’ academic achievement, while the remaining 16.4% was influenced by other factors. The findings suggest the importance of optimizing personal-social guidance services provided by school counselors and strengthening parent-school partnerships to support students’ academic success.